2020
DOI: 10.1186/s12992-019-0531-5
|View full text |Cite
|
Sign up to set email alerts
|

Globalization of national surgical, obstetric and anesthesia plans: the critical link between health policy and action in global surgery

Abstract: Efforts from the developed world to improve surgical, anesthesia and obstetric care in low- and middle-income countries have evolved from a primarily volunteer mission trip model to a sustainable health system strengthening approach as private and public stakeholders recognize the enormous health toll and financial burden of surgical disease. The National Surgical, Obstetric and Anesthesia Plan (NSOAP) has been developed as a policy strategy for countries to address, in part, the health burden of diseases amen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
183
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(199 citation statements)
references
References 13 publications
9
183
5
2
Order By: Relevance
“…They are central to defining the role of surgery within the broader national health strategy, but the competing health priorities introduced by the pandemic have endangered the ongoing progress of NSOAP development, funding, and implementation. A forum for national surgical planning scheduled for early 2020 incorporating Latin American countries [46] has had to be postponed as well as a ''highlevel workshop on NSOAP'' in Nepal organised by UNI-TAR, the Global Surgery Foundation and the Nepalese government [47].…”
Section: Governancementioning
confidence: 99%
“…They are central to defining the role of surgery within the broader national health strategy, but the competing health priorities introduced by the pandemic have endangered the ongoing progress of NSOAP development, funding, and implementation. A forum for national surgical planning scheduled for early 2020 incorporating Latin American countries [46] has had to be postponed as well as a ''highlevel workshop on NSOAP'' in Nepal organised by UNI-TAR, the Global Surgery Foundation and the Nepalese government [47].…”
Section: Governancementioning
confidence: 99%
“…A systematic review and meta-analysis on the prevalence of anxiety, depression, and stress among the general population during the COVID-19 revealed that 29.6% of participants had stress, 31.9% had anxiety and 33.7% had depression [ 13 ]. Another review and meta-analysis on the mental health impact of COVID-19 on health care professionals reported that anxiety, depression, and anxiety, was prevalent in 23·2%, 22·8%, and 38·9% of the study participants respectively [ 14 ].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Surgery is now firmly entrenched in healthcare systems as a part of the Universal Health Coverage goals [45]. A simple way for national governments to improve patient safety and save money is by investing in local public production of ABHRs, including centralized quality control laboratories, for their healthcare infrastructure.…”
Section: Resultsmentioning
confidence: 99%